PEMBUATAN FILM ANIMASI 2 DIMENSI â€œEKSPLORASI TRADISI ANTAR AJONGâ€ DI KABUPATEN SAMBAS - Winda Sari; Nia Safitri; Narti Prihartini; Vanie Wijaya (PROGRESS, 2023)
The Antar Ajong tradition is a Sambas community culture that is still preserved today. Antar Ajong is a series of traditional ceremonial rituals in the form of releasing a small lancang boat (Ajong) in the Coastal area in Paloh District and is carried out during the planting season, especially in planting rice. This research was conducted with the aim of introducing the Sambas culture of Antar Ajong tradition with 2-Dimensional Animation media. The survey results showed about 76.7% of Sambas local people and outsiders who did not know or did not know at all about the Antar Ajong tradition. This research uses the MDLC (Multimedia Development Life Cylce) Development method as a procedure or step in conducting research and stages of work consisting of 6 stages, concept, design, material collecting, assembly, testing, and distribution. The results of questionnaire testing to general public respondents received a score of 88.9%, which means that this animated film was successful in introducing and providing insight into the culture of the Antar Ajong Tradition through the media of 2-dimensional animated films to many people.